Periphyton-based cage culture of Nile tilapia: An interesting model for small-scale farming - Garcia, F.; Sabbag, O. J. [UNESP]; Kimpara, J. M.; Romera, D. M.; Sousa, N. S.; Onaka, E. M.; Ramos, I. P. [UNESP] (Elsevier, 2017)
We evaluated the production costs and the profitability of using bamboo substrates to enhance periphyton production in cages, in combination with a restricted diet and reduced stocking densities. Nile tilapia (46.56 ± 2.53 g) were placed in 21 cages, and the inclusion of bamboo substrates was evaluated in three different stocking densities (40, 60, and 80 kg of fish/m3) in association with two feeding schemes (100% and 50% of daily ration). No bamboo substrates were included in the control group. The inclusion of the bamboo substrates in cages increased fish weight gain, shortened the farming cycle length, and improved the feed conversion ratio. The proposed production model of Nile tilapia farming in cages with substrates offers a way for small-scale producers to increase the efficiency of the system with annual operating income up to 57% higher and the profitability index up to 87% higher than the currently used system adopted by Brazilian farmers.
Keywords: Economics; Oreochromis niloticus; Production cost; Profitability